THE IMPOSITION OF TAX ON INHERITANCE IN INDONESIA - Rieska Wulandari (Scientax, 2020)
Indonesia has enjoyed high and stable economic growth during the last decade. However, the benefits of growth have not been shared equally. Wealth inequality is widening in recent years which gives a serious threat to sustainable growth. The taxation policy still faces challenges to support inequality-reducing programs. The limitation of Personal Income Tax to conduct redistribution role and the absence of capital gain tax in Indonesia are some of the challenges faced in the fiscal policy field. Inheritance is assumed to be one of the sources of wealth accumulation. To reduce the gap between the richest and the rest, it is time for Indonesia to impose an inheritance tax . This paper examines the suitable inheritance tax design for Indonesia taking into consideration of experiences from a few selected countries. Based on the analysis, Indonesia should have an estate tax model with basic exemption starts from IDR 14.5 billion (USD 1 Million).